Construction of Green Fluorescent Protein-Tagged Aeromonas veronii for Understanding Its Pathogenicity in Rice-Field Eel (Monopterus albus) - Changtan Yang; Jiali Jin; Liyong Ye; Bo Liu; Huan Ye; Huamei Yue; Chuangju Li; Hanwen Yuan; Rui Ruan (Fishes, 2026)
The rice-field eel (Monopterus albus) is an important economic aquaculture species in China. Aeromonas veronii is one of the most common pathogens, which has a high infection and mortality rate in rice-field eel culture. In this study, a strain of A. veronii (AV-MA), isolated from the intestine of a diseased rice-field eel, was labelled with green fluorescent protein (GFP) using mini-Tn7-based systems. The growth curve and virulence of the GFP-labelled AV-MA (AV-MAGFP) strain showed no significant differences compared to AV-MA. After immersion infection with AV-MAGFP at 2.5 × 109 CFU/mL, bacterial loads in the liver, stomach, intestine, spleen, kidney, and heart tissues peaked within 1–6 h, and then declined gradually over time. AV-MAGFP infection remarkably increased intestinal malondialdehyde (MDA) content, superoxide dismutase (SOD) and catalase (CAT) activities. Levels of interleukin-8 (IL-8), interleukin-10 (IL-10), Tumor necrosis factor-α (TNF-α) and nuclear factor kappa-B repressing factor (nkrf) mRNAs fluctuated in the intestine after infection. In conclusion, this study demonstrated that GFP DNA was inserted into the chromosome of A. veronii using mini-Tn7 system for tracking its invasion pathway in vivo of rice-field eels, which provides a useful tool for further studying the pathogen–host interaction mechanisms between A. veronii and M. albus.